PREDIKSI PRODUKSI JAGUNG DALAM MODEL PENYEDIAAN TEPUNG JAGUNG PADA RANTAI PASOK JAGUNG - Dorina Hetharia; M. Syamsul Maarif; Yandra Arkeman; Titi Candra S. (JURNAL TEKNIK INDUSTRI, 2016)
Corn flour as one of the products made from corn is an intermediate product. This productcan be consumed directly, also can be used as raw materials in the food industry, feedindustry and other industrial raw materials. In the supply chain system, corn flour industry isa part of the maize supply chain . To maintain the continuity of the flow of raw materials inthe supply chain , the industry needs to provide corn flour that meets quantity with goodquality according to consumer demand . It is closely related to the supply of corn as a rawmaterial for corn flour. The provision of corn are also closely related to the availability ofthe amount of corn production obtained from the farmers. This paper discussed aboutprediction of maize production using artificial neural networks and a statistical forecasting .The input variables of corn production forecast in causal models were land and rainfall,while the output variable was the amount of corn production per month . The forecastingresults would be used as input for the corn flour industry.